2021
DOI: 10.3390/ijerph18126602
|View full text |Cite
|
Sign up to set email alerts
|

Description of Lifestyle, Including Social Life, Diet and Physical Activity, of People ≥90 years Living in Ikaria, a Longevity Blue Zone

Abstract: A cross-sectional observational study was conducted to describe the lifestyle of people ≥90 years, living in Evdilos or Raches, two municipalities of the Greek island of Ikaria, classified a longevity blue zone. The 71 participants were interviewed and underwent the Mediterranean Islands study food frequency questionnaire (MEDIS-FFQ) and the international physical activity questionnaire (IPAQ). The frequency of social contacts was daily for 77.9% of participants, weekly for 16.1%, and monthly for 5.9%. Most pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
0
38
0
1
Order By: Relevance
“…The following activity was categorized as low intensity: Basho-fu weaving which was described as the most labour-intensive activity as it was a continuous task completed throughout 20 days, however, it involved hand dexterity, fine gross motor skills and precision (Willcox et al, 2007b). Moderate intensity activities were categorized in studies as the following: swimming, dancing and walking that were identified as modes of aerobic moderate intensity (Legrand et al, 2021); shepherd work had been labeled as constant and continuous energy expenditure walking long distances in the mountainous terrain (Pes et al, 2013); outdoor hobbies and nature engagement are broader terms that have been categorized as moderate intensity activities relating to swimming and gardening outdoor tasks using both upper and lower limbs which were identified as such by Legrand et al (2019) and Nicklett et al (2016); housekeeping pertaining to household chores that involve vacuuming, mopping, washing windows, etc., have met the metabolic equivalent value of 3.0 equating to moderate intensity activities (Manini et al, 2006). High intensity was categorized between the remaining activities, farming, and other labour occupations.…”
Section: Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The following activity was categorized as low intensity: Basho-fu weaving which was described as the most labour-intensive activity as it was a continuous task completed throughout 20 days, however, it involved hand dexterity, fine gross motor skills and precision (Willcox et al, 2007b). Moderate intensity activities were categorized in studies as the following: swimming, dancing and walking that were identified as modes of aerobic moderate intensity (Legrand et al, 2021); shepherd work had been labeled as constant and continuous energy expenditure walking long distances in the mountainous terrain (Pes et al, 2013); outdoor hobbies and nature engagement are broader terms that have been categorized as moderate intensity activities relating to swimming and gardening outdoor tasks using both upper and lower limbs which were identified as such by Legrand et al (2019) and Nicklett et al (2016); housekeeping pertaining to household chores that involve vacuuming, mopping, washing windows, etc., have met the metabolic equivalent value of 3.0 equating to moderate intensity activities (Manini et al, 2006). High intensity was categorized between the remaining activities, farming, and other labour occupations.…”
Section: Data Synthesismentioning
confidence: 99%
“…General study characteristics were extracted to provide a synthesized understanding of periods of publication, countries of publication, study designs and populations studied (Table 3). Analysis of these themes was drawn from the increased number of studies in certain categories, with a significant portion of studies conducted in the last five years (Fastame et al, 2018;Legrand et al, 2019Legrand et al, , 2021Madrigal-Leer et al, 2020;Nieddu et al, 2020;Pes et al, 2018Pes et al, , 2020Pes et al, , 2021Spencer-Hwang et al, 2018) and being primarily of a cross sectional design and published in the United States (Chan et al, 1997;Legrand et al, 2019;Panagiotokos et al, 2011;Pes et al, 2018Pes et al, , 2020Spencer-Hwang et al, 2018;Willcox et al, 2007bWillcox et al, , 2008 with cross-sectional study designs (11 out of 18, level IV evidence) utilizing questionnaires were the most common research tool (Akisaka et al, 1996;Chan et al, 1997;Deiana et al, 1999;Fastame et al, 2018;Legrand et al, 2019;Legrand et al, 2021;Madrigal-Leer et al, 2020;Nieddu et al, 2020;Panagiotakos et al, 2011;Pes et al, 2013Pes et al, , 2018. Populations that were investigated most commonly were Okinawan resident centenarians (Akisaka et al, 1996;Chan et al, 1997;Willcox et al, (2007a)) and centenarian residents of municipalities in Sardinia (Deiana et al, 1999;Pes et al, 2013;Poulain et al, 2004).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the overall assessment of dietary habits of Ikarian centenarians, evaluated through a special diet score, did not provide data concerning average caloric intake, but only indicated greater adherence to the Mediterranean dietary pattern, and consequently, healthier dietary habits [ 31 ]. However, the results of a subsequent study [ 27 ] showed that existing data regarding the Mediterranean diet as a determining factor leading to longevity are less convincing in comparison to other environmental factors, such as family solidarity, social interaction, and physical activity.…”
Section: Introductionmentioning
confidence: 99%